Analisis Kesulitan Belajar Siswa Sekolah Dasar pada Pembelajaran Ilmu Pengetahuan Alam - Rahmah, Nur; Afifa, Nur (Jurnal Didaktika Pendidikan Dasar, 2023)
The purpose of this study was to determine the factors causing learning difficulties of public elementary school students No. 1 Pesaku in learning science lessons. This research method uses a qualitative descriptive method, where the research instruments are teacher and student interviews, questionnaires, documentation and student daily test scores. After teaching and learning activities, interviews were conducted to see students' learning abilities and the teacher's constraints in delivering the material. Questionnaire to identify student learning difficulties. Daily test scores are used to determine the extent of student learning problems. Documentation as supporting and complementary data for the use of observation and interview methods. The subjects of this research were the fifth grade students of SD No. 1 pesaku together with the homeroom teacher. The results of this study indicate that the causes of student learning difficulties consist of two factors, namely internal factors, namely student interest in learning, students' attitudes towards learning and study habits, while external factors are parents' attention to learning, the student's learning activities are lacking, the condition of the school environment and media or tools available in schools are inadequate.